Factors Affecting Successful CPR in Covid-19 Patients: a Systematic Literature Review - Maisyaroh, Arista; Widianto, Eko Prasetya; Kurnianto, Syaifuddin; Fitria, Riris Lailatul (Universitas Airlangga, 2022)
Introduction: : Cardiac arrest is a sudden cessation of ineffective pumping. Cardio-pulmonal-resuscitation (CPR) applied to save the life among those with cardiac arrest. During the pandemic COVID-19 patients, cardiac arrest was found as the major causes of death Even cardio-pulmonal-resuscitation (CPR) applied to save the life, a few of them was survived. The purpose of this review is to determine the quality of life in COVID-19 patients with CPR post cardiac arrest. Method: The paper research was reviewed regarding their inclusion criteria and quality assessment using the Joana Briggs Institute's critical appraisal checklist. Three academic databases; PubMed, Springerlink, and Science direct were comprehensively applied to collect the published article from 2017 to 2020. They are Articles were selected by PRISMA 2020 flow diagram for systematic review. Results: A total 10 studies were yielded in the final analysis. Factor affecting successful CPR in COVID-19 patient post cardiac arrest were; duration of CPR was delivered between six to 20 minutes. In comparison to the situation before thepandemic COVID-19, less neurological function improvement was signed of lowering quality of life of CPR patients with COVID-19. Conclusion: This study highlighted the quality of life in COVID-19 patients with cardiac arrest and conducted CPR was poorer compared to those before the pandemic. Findings considered COVID-19 placed cardiac arrest survivor in a higher risk of morbidity and mortality. Future study determines factors associated with higher probabilities of surviving after CPR delivered among patient with COVID-19 post cardiac is highly recommended.